(untitled) (REMUNOM, 2025)
Infectious pododermatitis is one of the main causes of lameness in sheep and goats, generating significant losses due to reduced productive and reproductive performance of the animals. The disease is mainly caused by the bacteria Dichelobacter nodosus and Fusobacterium necrophorum, whose interaction, associated with environmental factors such as humidity and inadequate management, favors the establishment and progression of foot lesions. This study gathers updated information on the pathological aspects, clinical signs, diagnosis, and treatment strategies of the disease, highlighting the differences in susceptibility between sheep and goats. The review highlights the importance of early diagnosis and prophylactic measures, including sanitary management, environmental corrections, and microbiological control, as essential tools to minimize the spread of the disease and mitigate its economic impacts on sheep and goat farming.